A nanobody that recognizes a 14-residue peptide epitope in the E2 ubiquitin-conjugating enzyme UBC6e modulates its activity. (October 2019) - Ling, Jingjing; Cheloha, Ross W.; McCaul, Nicholas; Sun, Zhen-Yu J.; Wagner, Gerhard; Ploegh, Hidde L.
Highlights: Identified single domain antibodies (VHHs) that bind to UBC6e with high affinity. VHH binds to a short linear epitope near a phosphorylation site. VHH binding to UBC6e enhances enzymatic activity. VHH binding inhibits UBC6e phosphorylation in cells. Abstract: A substantial fraction of eukaryotic proteins is folded and modified in the endoplasmic reticulum (ER) prior to export and secretion. Proteins that enter the ER but fail to fold correctly must be degraded, mostly in a process termed ER-associated degradation (ERAD). Both protein folding in the ER and ERAD are essential for proper immune function. Several E2 and E3 enzymes localize to the ER and are essential for various aspects of ERAD, but their functions and regulation are incompletely understood. Here we identify and characterize single domain antibody fragments derived from the variable domain of alpaca heavy chain-only antibodies (VHHs or nanobodies) that bind to the ER-localized E2 UBC6e, an enzyme implicated in ERAD. One such VHH, VHH05 recognizes a 14 residue stretch and enhances the rate of E1-catalyzed ubiquitin E2 loading in vitro and interferes with phosphorylation of UBC6e in response to cell stress. Identification of the peptide epitope recognized by VHH05 places it outside the E2 catalytic core, close to the position of activation-induced phosphorylation on Ser184. Our data thus suggests a site involved in allosteric regulation of UBC6e's activity. This VHH should be useful not only to dissect the participation of UBC6e in ERAD and in response to cell stress, but also as a high affinity epitope tag-specific reagent of more general utility.